2022
DOI: 10.1021/acsomega.2c03908
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticancer Evaluation of Novel Indole Based Arylsulfonylhydrazides against Human Breast Cancer Cells

Abstract: A series of novel indole based sulfonohydrazide derivatives (5a−k) containing morpholine heterocyclic ring were synthesized through multistep chemical reactions. The target compounds (5a−k) were prepared by the reaction of substituted phenyl sulfonylhydrazides (2a−k) with morpholine derivative of indole 3-carboxaldehyde. All the target compounds were screened for their anticancer activity in vitro against the estrogen receptor-positive breast cancer line MCF-7 and triple-negative breast cancer cell line, MDA-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Indole‐sulfonylhydrazide hybrid 57 (IC 50 : 13.2 and 8.2 µM) exhibited strong anti‐MCF‐7 and anti‐MDA‐MB‐231 cell activity and was nontoxic (IC 50 : >100 µM) to normal HEK 293 cells. [ 97 ] The SAR revealed that morpholine at the N‐1 position of indole moiety was unnecessary for the activity, while the introduction of chloro into the C‐5 position increased the activity, as evidenced by the high anti‐MCF‐7 and anti‐MDA‐MB‐231 cell activity of hybrid 58 (IC 50 : 0.5 and 0.9 µM). [ 98 ]…”
Section: Indole/isatin‐sulfonamide/sulfonate/sulfonylhydrazide Hybridsmentioning
confidence: 99%
“…Indole‐sulfonylhydrazide hybrid 57 (IC 50 : 13.2 and 8.2 µM) exhibited strong anti‐MCF‐7 and anti‐MDA‐MB‐231 cell activity and was nontoxic (IC 50 : >100 µM) to normal HEK 293 cells. [ 97 ] The SAR revealed that morpholine at the N‐1 position of indole moiety was unnecessary for the activity, while the introduction of chloro into the C‐5 position increased the activity, as evidenced by the high anti‐MCF‐7 and anti‐MDA‐MB‐231 cell activity of hybrid 58 (IC 50 : 0.5 and 0.9 µM). [ 98 ]…”
Section: Indole/isatin‐sulfonamide/sulfonate/sulfonylhydrazide Hybridsmentioning
confidence: 99%
“…Molecular hybridization synergizes the individual therapeutic potential of constituent moieties and upsurges the capacity to inhibit multiple biotargets. Several heterocyclic frameworks containing indole and thiadiazole motifs exhibit notable anti‐breast cancer efficacy, as shown in Figure 2 [32–37] . Considering the remarkable anti‐breast cancer efficacy of indole and thiadiazole derivatives, a new class of indole‐linked 1, 3, 4‐thiadiazole framework is explored in the present report for potential anti‐breast cancer action.…”
Section: Introductionmentioning
confidence: 96%
“…Several heterocyclic frameworks containing indole and thiadiazole motifs exhibit notable anti-breast cancer efficacy, as shown in Figure 2. [32][33][34][35][36][37] Considering the remarkable anti-breast cancer efficacy of indole and thiadiazole derivatives, a new class of indole-linked 1, 3, 4-thiadiazole framework is explored in the present report for potential anti-breast cancer action.…”
Section: Introductionmentioning
confidence: 99%
“…[27,28] Different indole ring substitutions in compounds can enhance their ability to inhibit the proliferation of cancer cells. [29][30][31][32][33] Based on a literature analysis, in this review we have summarized and highlighted the indole derivatives as CBS inhibitors (discovered after 2018). We have also discussed the structure-activity relationship (SAR) of indole derivatives as CBS inhibitors.…”
mentioning
confidence: 99%